3-[2-(5H-Indolo[2,3-b]quinoxalin-5-yl)ethyl]-1,3-oxazolidin-2-one - Alsubari, A.; Bouhfid, R.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C(19)H(16)N(4)O(2), has an almost planar fused N-heterocyclic system (r.m.s. deviation = 0.031 angstrom) and an almost planar five-membered 1,3-oxazolidine ring (r.m.s. deviation = 0.015 angstrom) at the ends of an ethylene chain [N-C-C-N torsion angle = -65.6 (2)degrees]. The ring systems are inclined at 38.1 (1)degrees to one another.